Eccrine chromhidrosis in severe acute respiratory syndromecoronavirus- 2 virus infection treated with favipiravir - Müge Göre Karaali; Gizem Issın; Soner Karaali; Şevki Özdemir (Galenos Publishing House, 2022)
Coronavirus disease-2019 (COVID-19) caused by the severe acute respiratory syndrome-coronavirus-2, which became a pandemic, may have cutaneous findings. Eccrine chromhidrosis is a rare disorder characterized by the excretion of colored sweat via the eccrine sweat glands. We present eccrine chromhidrosis in two COVID-19 cases treated with favipiravir.